Effects of cortisol on the heart: characterization of myocardial involvement in cushing's disease by longitudinal cardiac MRI T1 mapping. Issue 1 (9th July 2016) - Roux, Charles; Kachenoura, Nadjia; Raissuni, Zainab; Mousseaux, Elie; Young, Jacques; Graves, Martin J.; Jublanc, Christel; Cluzel, Philippe; Chanson, Philippe; Kamenický, Peter; Redheuil, Alban
Abstract : Purpose: Cushing's disease (CD) is associated with alterations in cardiac geometry and function, shown to be reversible after treatment. Our aim was to study cortisol‐related changes in myocardial content in CD at baseline and after treatment using MR myocardial T1 times. Materials and Methods: This is a longitudinal study performed in 10 patients with active CD matched with 10 hypertensive and 10 healthy controls. All subjects had MR after CD diagnosis and 6 months after cortisol normalization. The 1.5 Tesla MR protocol included left ventricular geometry and function assessment and MOLLI sequences before and after contrast injection as well as late gadolinium enhancement. Results: At baseline, native myocardial T1 was significantly higher in CD patients compared with controls and the hypertensive group (1056 ± 139 ms versus 929 ± 80 ms, P  = 0.023; 1056 ± 139 ms versus 952 ± 51, P  = 0.049). After treatment, native and postcontrast myocardial T1 decreased in CD patients versus controls (1056 ± 139 ms versus 832 ± 78, P  = 0.006 and 483 ± 69 ms versus 395 ± 39 ms, P  = 0.010) reaching values even lower than found in controls ( P  = 0.038 and P  = 0.001, respectively). Conclusion: Native myocardial T1 is increased in Cushing's disease independently from hypertension and notably decreases after effective treatment, highlighting its potential to detect subclinical diffuse myocardial involvement in this condition. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:147–156.